English Teachers' Barriers in Implementing 2013 Curriculum Revision Edition in Teaching English - Indrawatiyaningsih Ngkeja; Vivin Krismawanti Modjanggo (Sintuwu Maroso Journal of English Teaching, 2022)
The purpose of this research is to determine the barriers experienced by English teacher in implementing 2013 curriculum revision edition in teaching English. This research uses a qualitative descriptive study. The researchers use observation, interview, and documentation in the form of syllabus, lesson plan, and pictures to collect the data. The research subject is English teacher and seventh grade students of SMP Negeri 1 Tojo Barat that consists of six study groups. The result of the research shows that English teacher experienced external barriers and internal barriers. The external barriers are obstacles that come from outside the English teacher, namely: (1) covid-19 pandemic (2) the barriers from the government, (3) the barriers from the schools, and (4) the barriers from students. Internal barriers are obstacles that come from within the English teacher itself, namely: (1) the barriers in making lesson plans, (2) the barriers in the learning process, and (3) the barriers in making evaluation.